2011
DOI: 10.1002/hyp.8200
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fibre‐optic distributed temperature sensing to traditional methods of evaluating groundwater inflow to streams

Abstract: Abstract:There are several methods for determining the spatial distribution and magnitude of groundwater inputs to streams. We compared the results of conventional methods [dye dilution gauging, acoustic Doppler velocimeter (ADV) differential gauging, and geochemical end-member mixing] to distributed temperature sensing (DTS) using a fibre-optic cable installed along 900 m of Ninemile Creek in Syracuse, New York, USA, during low-flow conditions (discharge of 1Ð4 m 3 s 1 ). With the exception of differential ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
124
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(131 citation statements)
references
References 39 publications
7
124
0
Order By: Relevance
“…However, DTS and VTP measurements showed that the spatial distribution of groundwater discharge in this section is not homogeneous (Fig. 4), similarly to the DTS observations of Lowry et al (2007), Briggs et al (2011) and the VTP-based flux estimations of Schmidt et al (2007) and Anibas et al (2011). The large spatial variability in groundwater discharge is most likely due to heterogeneity in streambed hydraulic conductivity (Kalbus et al, 2006;Sebok et al, 2014), which was also suggested by the streambed composition with interchanging sand, gravel and clusters of macrophyte growth.…”
Section: Spatial Variability and Magnitude Of Groundwater Discharge Fsupporting
confidence: 70%
See 4 more Smart Citations
“…However, DTS and VTP measurements showed that the spatial distribution of groundwater discharge in this section is not homogeneous (Fig. 4), similarly to the DTS observations of Lowry et al (2007), Briggs et al (2011) and the VTP-based flux estimations of Schmidt et al (2007) and Anibas et al (2011). The large spatial variability in groundwater discharge is most likely due to heterogeneity in streambed hydraulic conductivity (Kalbus et al, 2006;Sebok et al, 2014), which was also suggested by the streambed composition with interchanging sand, gravel and clusters of macrophyte growth.…”
Section: Spatial Variability and Magnitude Of Groundwater Discharge Fsupporting
confidence: 70%
“…Thus, the detection and quantification of groundwatersurface water dynamics present a challenge, particularly in lowland streams. In these streams the diffuse groundwater discharge along the stream channel reduces the sensitivity of thermal methods (Lowry et al, 2007;Krause et al, 2012), as well as tracer methods (Gonzales et al, 2009), and can cause low net increase in stream flow which also limits the available methods for detecting groundwater discharge (Briggs et al, 2011). At the same time due to the presence of focused, significant discharge zones (Lowry et al, 2007;Matheswaran et al, 2012) the spatial variability of groundwater discharge can be large (Krause et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations